Randomized, Controlled Trial Comparing Mitral Valve Repair With Leaflet Resection Versus Leaflet Preservation on Functional Mitral Stenosis: The CAMRA CardioLink-2 Study. Issue 14 (6th October 2020) - Chan, Vincent; Mazer, C. David; Ali, Faeez Mohamad; Quan, Adrian; Ruel, Marc; de Varennes, Benoit E.; Gregory, Alexander J.; Bouchard, Denis; Whitlock, Richard P.; Chu, Michael W.A.; Dokollari, Aleksander; Mesana, Thierry; et al.
Abstract : Background: Equipoise exists between the use of leaflet resection and preservation for surgical repair of mitral regurgitation caused by prolapse. We therefore performed a randomized, controlled trial comparing these 2 techniques, particularly in regard to functional mitral stenosis. Methods: One hundred four patients with degenerative mitral regurgitation surgically amenable to either leaflet resection or preservation were randomized at 7 specialized cardiac surgical centers. Exclusion criteria included anterior leaflet or commissural prolapse, as well as a mixed cause for mitral valve disease. Using previous data, we determined that a sample size of 88 subjects would provide 90% power to detect a 5–mm Hg difference in mean mitral valve gradient at peak exercise, assuming an SD of 6.7 mm with a 2-sided test with α=5% and 10% patient attrition. The primary end point was the mean mitral gradient at peak exercise 12 months after repair. Results: Patient age, proportion who were female, and Society of Thoracic Surgeons risk score were 63.9±10.4 years, 19%, and 1.4±2.8% for those who were assigned to leaflet resection (n=54), and 66.3±10.8 years, 16%, and 1.9±2.6% for those who underwent leaflet preservation (n=50). There were no perioperative deaths or conversions to replacement. At 12 months, moderate mitral regurgitation was observed in 3 subjects in the leaflet resection group and 2 in the leaflet preservation group. The mean transmitral gradient at 12 months during peak exercise was 9.1±5.2 mm Hg after leaflet resection and 8.3±3.3 mm Hg after leaflet preservation ( P =0.43). The participants had similar resting peak (8.3±4.4 mm Hg versus 8.4±2.6 mm Hg; P =0.96) and mean resting (3.2±1.9 mm Hg versus 3.1±1.1 mm Hg; P =0.67) mitral gradients after leaflet resection and leaflet preservation, respectively. The 6-minute walking distance was 451±147 m for those in the leaflet resection versus 481±95 m for the leaflet preservation group ( P =0.27). Conclusions: In this adequately powered randomized trial, repair of mitral prolapse with either leaflet resection or leaflet preservation was associated with similar transmitral gradients at peak exercise at 12 months postoperatively. These data do not support the hypothesis that a strategy of leaflet resection (versus preservation) is associated with a risk of functional mitral stenosis. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier NCT02552771. Abstract : Supplemental Digital Content is available in the text.